The sensitivity of Value-at-Risk estimates using Monte Carlo approach - Christos Agiakloglou; Charalampos Agiropoulos (SPOUDAI - Journal of Economics and Business, 2011)
This study examines the sensitivity of VaR estimates obtained with Monte Carlo technique using the data set of Benninga and Wiener (1998) and applies the Kupiec test either by assuming large sample properties or by obtaining p-values through simulation process.
Keywords: G32; 330; VaR; Monte Carlo method; Kupiec test